Reduced white matter venous density on MRI is associated with neurodegeneration and cognitive impairment in the elderly - Li, Chenyang; Rusinek, Henry; Chen, Jingyun; Bokacheva, Louisa; Vedvyas, Alok; Masurkar, Arjun V.; Haacke, E. Mark; Wisniewski, Thomas; Ge, Yulin (Frontiers in Aging Neuroscience, 2022)
High-resolution susceptibility weighted imaging (SWI) provides unique contrast to small venous vasculature. The conspicuity of these mesoscopic veins, such as deep medullary veins in white matter, is subject to change from SWI venography when venous oxygenation in these veins is altered due to oxygenated blood susceptibility changes. The changes of visualization in small veins shows potential to depict regional changes of oxygen utilization and/or vascular density changes in the aging brain. The goal of this study was to use WM venous density to quantify small vein visibility in WM and investigated its relationship with neurodegenerative features, white matter hyperintensities (WMHs), and cognitive/functional status in elderly subjects(N = 137). WM venous density was significantly associated with neurodegeneration characterized by brain atrophy (β= 0.046±0.01, p<0.001), but no significant association was found between WM venous density and WMHs lesion load (p=0.3963). Further analysis of clinical features revealed a negative trend of WM venous density with the sum-of-boxes of Clinical Dementia Rating and a significant association to category fluency (one-minute animal naming). These results suggest that WM venous density on SWI can be used as a sensitive marker to characterize cerebral oxygen metabolism and different stages of cognitive and functional status in neurodegenerative diseases.